On the Fate of the Temporal Existence of Man in the Technogenic Epoch: between Moments and Minutes - N. V. Serova (Дискурс)
Introduction.In the technogenic epoch, people’s understanding of the nature of time has changed. The image of the high-tech time has formed and widely spread under the influence of modern technologies. Today, it has determined the nature of the temporal existence of person and has become, through the electronic clock, an instrument of its dehumanization. Anticipating these threats, the representatives of existentialism undertook the development of temporal problems starting from the middle of the XIX century. The existential analysis of the category “instant” as a specific dimension of the temporal existence of a person has taken a central place in it. Identifying the differences in the meaning of the terms “instant” and “minute” in philosophical and natural science interpretations, the author has suggested the possibility of humanizing modern technological processes by changing modern person’s concept of time.Methodology and sources. Hermeneutical and retrospective methods, methods of existential and comparative analyzes, the use of existential, cultural and interdisciplinary approaches have become the methodological basis of the work. The analysis of philosophical texts on the problem of changing the perception of time by person in the technogenic epoch (L. Mumford, M. McLuhan, D. Naisbitt), the works of existential philosophers devoted to temporal problems (S. Kierkegaard, N. Berdyaev, M. Heidegger) theoretical works on physics (S. Hawking, E. Sudarshan, J. Vaccaro), and a number of works on the humanitarian problems of the technogenic epoch was made (E. Balas, V. Tikhonova, V. Stepin, L. Kuznetsova).Results and discussion. The problem of overcoming the dehumanization of the temporality of human existence under the influence of high-tech time was considered in the article. The following conclusions were the results of the study of this problem. First, the reasons for the dehumanization of the temporal existence of a person acting in accordance with high-tech time have been identified. Secondly, the need to distinguish between the concepts of “minutes” of objective time and “moments” of the temporality of human existence was justified. Third, the study of temporal problems was defined as a condition for the humanization of scientific and technological development of modern epoch.Conclusion. In the technogenic, person’s free choice between minutes of high-tech time and moments of existential time have determined the fate of his / her temporal existence. Making one’s choice, a person has determined the character of the development of the technogenic epoch in the direction of the dehumanization of human existence or in the direction of the humanization of the technical world. The breadth of the study of the nature of human temporality and temporal issues in general will have affected the right choice.